The Influence of Comorbidity on Health-Related Quality of Life After Esophageal Cancer Surgery - Backemar, Lovisa (Ann Surg Oncol, 2020)
BACKGROUND: Esophageal cancer surgery reduces patients’ health-related quality of life (HRQoL). This study examined whether comorbidities influence HRQoL in these patients. METHODS: This prospective cohort study included esophageal cancer patients having undergone curatively intended esophagectomy at St Thomas’ Hospital London in 2011–2015. Clinical data were collected from patient reports and medical records. Well-validated cancer-specific and esophageal cancer-specific questionnaires (EORTC QLQ-C30 and QLQ-OG25) were used to assess HRQoL before and 6 months after esophagectomy. Number of comorbidities, American Society of Anesthesiologists physical status classification (ASA), and specific comorbidities were analyzed in relation to HRQoL aspects using multivariable linear regression models. Mean score differences with 95% confidence intervals were adjusted for potential confounders. RESULTS: Among 136 patients, those with three or more comorbidities at the time of surgery had poorer global quality of life and physical function and more fatigue compared with those with no comorbidity. Patients with ASA III–IV reported more problems with the above HRQoL aspects and worse social function and pain compared with those with ASA I–II. Cardiac comorbidity was associated with worse global quality of life and dyspnea, while pulmonary comorbidities were related to coughing. Patients assessed both before and 6 months after surgery (n = 80) deteriorated in most HRQoL aspects regardless of comorbidity status, but patients with several comorbidities had worse physical function and fatigue and more trouble with coughing compared with those with fewer comorbidities. CONCLUSION: Comorbidity appears to negatively influence HRQoL before esophagectomy, but appears not to severely impact 6-month recovery of HRQoL.